The electrophysiological characteristics of social exclusion: the perspective of close and distant relationships - Zhang, Pengcheng; Zhu, Min; Hu, Jingjing; Gao, Xiangping (Frontiers in Psychology, 2023)
The sources of social exclusion are very wide, ranging from the closest people to strangers. However, current studies mainly reveal the electrophysiological characteristics of social exclusion by means of binary comparison between social exclusion and social inclusion, and lack of in-depth analysis of the differences caused by different sources of exclusion. In this study, a static passing ball paradigm including close and distant relationship identity information was used to reveal the electrophysiological characteristics of individuals when they were excluded by people with different close and distant relationship. The results showed that there was a degree effect of P2, P3a and LPC components when individuals were excluded by people with different close and distant relationship. Specifically, the amplitude of P2, P3a and LPC components was larger when individuals were excluded by more distant people. The results indicated that individuals would become more alert and perceive stronger exclusion experience when they were excluded by more distant people, which provided more diversified evidence for the conclusion that electrophysiological components were larger under the condition of exclusion, and revealed the electrophysiological basis behind the multiple motivation model. The results also helped to explain the physiological reasons behind individuals' different coping behaviors towards excluder with different importance of relationship.